2019
DOI: 10.1002/ijc.32505
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1 in patient‐derived bladder cancer spheroids activates retinoic acid signaling leading to TUBB3 overexpression and tumor progression

Abstract: Acquired chemoresistance is a critical issue for advanced bladder cancer patients during long‐term treatment. Recent studies reveal that a fraction of tumor cells with enhanced tumor‐initiating potential, or cancer stem‐like cells (CSCs), may particularly contribute to acquired chemoresistance and recurrence. Thus, CSC characterization will be the first step towards understanding the mechanisms underlying advanced disease. Here we generated long‐term patient‐derived cancer cells (PDCs) from bladder cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…The ALDH1A1-positive cell population is enriched in BC and its upregulation is associated with progression, aggressiveness, recurrence, shorter survival time, and a poor prognosis of BC [39,40]. Moreover, knockdown of the ALDH1A1 gene by the specific siRNA significantly decreased its clonogenicity and tumorigenic potential in bladder CSCs [39,41]. It is one of the top upregulated genes of BC organoids compared with normal bladder tissues [27].…”
Section: Role Of Aldh1a1mentioning
confidence: 99%
See 1 more Smart Citation
“…The ALDH1A1-positive cell population is enriched in BC and its upregulation is associated with progression, aggressiveness, recurrence, shorter survival time, and a poor prognosis of BC [39,40]. Moreover, knockdown of the ALDH1A1 gene by the specific siRNA significantly decreased its clonogenicity and tumorigenic potential in bladder CSCs [39,41]. It is one of the top upregulated genes of BC organoids compared with normal bladder tissues [27].…”
Section: Role Of Aldh1a1mentioning
confidence: 99%
“…Su et al found that ALDH1A1 + BC cells have higher clonogenicity and tumorigenicity than ALDH1A1 ones [39]. Recently, ALDH1A1 in patient-derived BC spheroids was shown to stimulate retinoic acid signaling, which leads to the overexpression of tubulin b III (TUBB3) and BC progression [41].…”
Section: Role Of Aldh1a1mentioning
confidence: 99%
“…However, these approaches fail to account for critical aspects of the TME. Indeed, (Yin et al, 2016) Bladder cancer (Namekawa et al, 2020) CAF-mediated interactions Lung cancer (Chen et al, 2018) Pancreatic cancer (Ware et al, 2016) Invasion Breast cancer (Avgustinova et al, 2016) Colon cancer (Nam et al, 2018) Colorectal cancer (Libanje et al, 2019) Vessel sprouting and intravasation Colon cancer (Ehsan et al, 2014) Niche activation and colonization Breast cancer (del Pozo Martin et al, 2015) High-throughput toxicology assay Breast cancer (Lee et al, 2008)…”
Section: Cancer Modeling Using Organotypic Modelsmentioning
confidence: 99%
“…Using multiple clinical specimens, we successfully identified cases in which a combination of disulfiram, an FDA approved drug for alcoholism, and cisplatin was predicted to produce synergy [41]. In another example of the potential superiority of 3D culture, Namekawa et al showed that ALDH1A1 expression was increased in T24 cells cultured in 3D compared to 2D cultures and that ALDH1A1 inhibition in patient-derived spheroids and mouse models suppressed the tumor growth [42].…”
Section: Strategies Using Complementarity Between Pdx and 3d Culturementioning
confidence: 99%